2005
DOI: 10.3208/sandf.45.4_61
|View full text |Cite
|
Sign up to set email alerts
|

AN INTERPRETATION OF SUBLOADING <I>t</I><SUB>ij</SUB> MODEL IN THE CONTEXT OF CONVENTIONAL ELASTOPLASTICITY THEORY

Abstract: An isotropic hardening elastoplastic model, named subloading ti;, has been recently proposed (Nakai and Hinokio, 2004). Three features differentiate subloading ti; model from the conventional ones: (a) the use of a modified stress space given by tensor ti;; (b) the split of the plastic strain increments in two components and (c) the use of two yield surfaces based on the concept of subloading. These three characteristics greatly improve the prediction capabilities of the model, with respect to those of the wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…1, where e NC stands for 'void ratio at the normal consolidation line'. Also, in this figure, t NC , t N1 , and t N1e indicate the modified mean pressure correspondent to the void ratio e NC , size of the subloading surface, and size of the normal yield surface, respectively (see details in [14,24]). The outer surface (normal) corresponds to those from conventional plasticity, but in this model it is required only to provide an asymptotic limit to the inner surface (subloading).…”
Section: The Subloading Tij Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…1, where e NC stands for 'void ratio at the normal consolidation line'. Also, in this figure, t NC , t N1 , and t N1e indicate the modified mean pressure correspondent to the void ratio e NC , size of the subloading surface, and size of the normal yield surface, respectively (see details in [14,24]). The outer surface (normal) corresponds to those from conventional plasticity, but in this model it is required only to provide an asymptotic limit to the inner surface (subloading).…”
Section: The Subloading Tij Modelmentioning
confidence: 99%
“…Based on the concepts briefly described above and using Tensor Analysis, Pedroso et al [24] deduced the constitutive relations of subloading tij model, in such a way that they resemble those of any conventional elastoplastic model, such as the modified Cam clay model [25].…”
Section: The Subloading Tij Modelmentioning
confidence: 99%
“…(42) also holds uniquely. Figure 18 shows a view of the yield surface of tij model in the principal spaces of sij and tij (Pedroso et al, 2005). The shape of the yield surface on the octahedral plane in the sij space is a rounded triangle and corresponds to that of the SMP criterion (Matsuoka and Nakai, 1974) ( see diagram (c)).…”
Section: Modeling the In‰uence Of The Intermediate Principal Stressmentioning
confidence: 99%
“…This tensor transformation allowed them to incorporate the eŠect of the intermediate principal stress implicitly. Nakai and Matsuoka (1986), , Matsuoka et al (1990) and Pedroso et al (2005) demonstrated the models capability. Their most notable contributions being (i) incorporating the subloading surface concept ( see later) to predict the behavior of overconsolidated soils and the eŠect of density and pressure on the mechanical behavior including the cyclic behavior and (ii) splitting the plastic strains into one computed from the ‰ow rule and the other with additional isotropic plastic component, which provides a stress path dependent strain increment (Nakai and Hinokio, 2004).…”
Section: Modiˆed Stress Tensor-an Alternative Approach To Model Complmentioning
confidence: 99%